Genetics and stability of the “Oly” dominant male sterile wheat mutant - Villaseñor Mir Héctor Eduardo; Huerta Espino, Julio; Espitia Rangelq, Eduardo; Hortelano Santa Rosa René; Rodríguez García Ma. Florencia; Martínez Cruz Eliel (Revista Mexicana de Ciencias Agrícolas, 2018)
The male sterility facilitated recurrent selection in wheat has not been extensively used, since the available male sterility sources do not allow the application of different selection techniques, are linked to deleterious effects or 100% fertile lines are difficult to generate. This paper aimed to present the male sterility source “Oly”, caused by a dominant mutant gene, obtained after 60Co gamma rays recurrent irradiation. The irradiation treatment began in 1996 and ended in 1998 and the seed irradiated for three cycles was massively reproduced. A completely sterile plant was identified and manually pollinated in the summer of 2000. Greenhouse and field evaluations in just over 7 000 plants showed that sterile plants always segregated 1:1 (sterile: fertile), their progenies were always 100% either fertile or sterile, fertile plants no longer segregated to sterile and 1:1 segregation was constant over different environments. The similarity test showed that the gene is not associated with deleterious effects and that was effective in the reconversion of elite material, and it will enable recurrent selection in wheat.